2021
DOI: 10.2147/idr.s320645
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Acinetobacter baumannii in Clinical Bacteremia Patients

Abstract: Introduction Colonization of the respiratory tract by Acinetobacter baumannii has been established as an independent risk factor for bacteremia. However, within-host evolution of A. baumannii in bacteremia has not been extensively investigated. Methods We performed whole-genome sequencing to discover the evolutionary characteristics that accompany the transition from respiratory tract carriage to bloodstream infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Our study also present divergences with previous studies on human infections. Indeed, we observed only few mutations in translational machinery genes or in genes related to replication, recombination, and repair (16, 46). However, these evolutions may have been shaped by alternative antibiotic treatments performed on human patients.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our study also present divergences with previous studies on human infections. Indeed, we observed only few mutations in translational machinery genes or in genes related to replication, recombination, and repair (16, 46). However, these evolutions may have been shaped by alternative antibiotic treatments performed on human patients.…”
Section: Discussionmentioning
confidence: 88%
“…Consequently, there remains a limited understanding of the fate of antibiotic resistance genes and more broadly of gene evolution post-antibiotic exposure and during host colonization. Seminal within-host microevolution studies on A. baumannii observed the accumulation of variations in genes involved surface structures such as motility, adhesion, biofilm formation or cell wall and capsule biogenesis, suggesting a consistent selective pressure during antibiotic-treated infections but phenotypic validation are usually missing (1416). Phenotypically, antibiotic exposure prompts bacteria to adopt a biofilm-like lifestyle, enhancing their resistance (17).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that genome changes occur in A. baumannii isolates during antibiotic treatment ( 26 , 27 ), during outbreaks ( 28 ), during studies in a hospital setting over a period of days ( 29 , 30 ), or on sampling of sites other than the digestive tract of a limited number of patients ( 31 33 ). It was found that genome changes due to mutation, recombination, and content can occur in a short period of days.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Also, it has been confirmed that the genome of bloodstream isolates was highly homologous to that of respiratory isolates, suggesting that A. baumannii BSI may originate from the respiratory tract. 44 At present, specimens for non-fermentative bacterial screening mainly include sputum, pharyngeal swabs, alveolar lavage fluid. Under the premise of ensuring the positive rate of bacterial screening, non-invasive methods were priority for specimen collection.…”
Section: Discussionmentioning
confidence: 99%